Externalidades positivas e o pagamento por serviços ambientais : uma promissora ferramenta de política ambiental - Régis, Adelmar Azevedo (2015)
This work analyzes the Payment for Environmental Services (PES) as a promising economic instrument to solve some problems related to environmental degradation and the generation of positive externalities. To achieve such goal, firstly the thesis analyzes concepts of externality and public goods and the main existing theories to tackle market failures, citing three specific environmental principles to combat negative and positive externalities: Polluter-Pays Principle, User-Pays Principle and Principle Protector-Receiver, which is the modern promotional function of law. Then, the thesis conducts a comparative analysis between the command and control instruments and economic instruments and their efficaciousness and cost-effectiveness in environmental preservation. With such a basis built, this work then defines environmental services and their types and promotes a literature review on the theoretical aspects that support PES schemes, as well as addresses two foreign case studies of PSA and some experiences in Brazil. This paper contributes to the theoretical development of the subject, still little explored in literature, and intends to demonstrate that the payment of environmental services is not a magical solution to the environmental crisis and did not appear to replace command and control instruments; it has to be added to current instruments of environmental policy, in order to correct market failures, which do not recognize the inherent value of ecosystem services and the benefits they provide to social welfare.